Partially hyperbolic random dynamics on Grassmannians - De Moor, Joris; Dorsch, Florian; Schulz-Baldes, Hermann (Journal of Mathematical Physics, 2023)
A sequence of invertible matrices given by a small random perturbation around a fixed diagonal partially hyperbolic matrix induces a random dynamics on the Grassmann manifolds. Under suitable weak conditions, it is known to have a unique invariant (Furstenberg) measure. The main result gives concentration bounds on this measure, showing that with high probability, the random dynamics stays in the vicinity of stable fixed points of the unperturbed matrix, in a regime where the strength of the random perturbation dominates the local hyperbolicity of the diagonal matrix. As an application, bounds on sums of Lyapunov exponents are obtained.
CRIS-Team Scopus Importer:2023-09-01